Transformation in Political Approach of Deoband for Freedom Movement (1920-1947) and its Reasons (Journal of Social Sciences Review, 2023)
This paper aims to explore the transformation that took place in the strategy of the Deoband School of thought in its struggle for independence from India. A descriptive role of the Deoband school of thought for the freedom of India was analyzed from its formation till 1947. Failure at the war of 1857, its founders, who were the heirs of Hazrat Shah Waliullah, upheld the spirit of freedom by establishing Darul Uloom Deoband. Deaband School of thought, under the leadership of Maulana Mahmud-ul-Hasan, moved a struggle to overthrow the British by force during the outbreak of the First World War. In the changing situation after the world war, the Deoband School of thought brought about a transformation in its political approach in its struggle for independence. This was the discarding of the violent method and adoption of the peaceful and constitutional struggle for achieving independence and securing the religious rights of the Muslims. The formation of Jamaitul Ulama-i-Islam was basically the beginning of the peaceful and constitutional struggle of Deoabnd. The peaceful and constitutional struggle of JUH in collaboration with the Indian National Congress testifies to the transformation.
Keywords: Deoband, British; Transformation; Freedom; Struggle; Maulana Mahmud-ul-Hasan; JUH; Congress